Eduard Hanslick - Sämtliche Schriften. Historisch-kritische Ausgabe Band I/6: Aufsätze und Rezensionen 1862-1863 - Hanslik, Eduard (Böhlau, 2008)
The present sixth volume of the new historic-critical complete edition of Eduard Hanslick´s works contains texts of the years 1862 to 1863, which are for the most part contributions from the Vienna "Presse". Some articles were published shortly after in national music journals such as the "Niederrheinische Musik-Zeitung" or the Berlin music journal "Echo". Hanslick revised som of them later for his well-known anthologies ("Die moderne Oper", aus dem Konzertsaal. Geschichte des Konzertwesens in Wien, II2). As before these texts were provided with lists of variant readings, which are printed subsequent to the respective article. The principles of publication were not changed. Minor variations are: different spelling, change from spaced writing to normal distance of characters or vice versa, smaller modification of the wording, updating or additions. Major changes mainly consist in leaving out large parts of the text or rearranging text passages from different sources to particular subjects. The fundamental change in Hanslick´s occupation as a critic as can be seen exactly from the 1860s, that is his stronger attention to reviewing the performance cannot be substantiated by his own editions so well because he often left out parts related to the concert. From that point of view this edition provides not only a better survey of the Vienna concert life in these years than Hanslick´s own edition but it also notes down in a much more precise way his changed approach to writing. Most of the texts, however, are completely unknown today. The main essay in the comment part deals with the music-aesthetic consequences of the phenomenon of boredom, the typical syndrome of the 19th century, which Hanslick´s reviews shed some light on. It becomes clear that there are more criteria in Hanslick that are important for an assessment of a work than those laid down in "Vom Musikalisch-Schönen". An important position in Hanslick´s life as a music critik take his trips to music festivals or world expositions. His travel diaries are still very informative and shown an open-minded cosmopolitan. Hanslick´s report on the bustle of the 1862 word exposition in London from an initially neutral attitude of an observer seems in a certain way to turn into a surrealistic inferno of the arising modern age and confirms unconsciously what Walter Benjamin realized first and formulated in his "Passagenwerk". This matter is dealt with a particular length in the notes, which as before briefly characterize, annotate or analyse for its aesthetic relevance every single text. Added to the annotations is an excerpt from a letter by August Wilhelm Ambros, which illustrates some aspects from Hanslick´s aesthetic of boredom from a different point of view.